The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1073/pnas.1115361109
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair-dependent mutagenesis in nondividing cells

Abstract: Mismatch repair (MMR) is a major DNA repair pathway in cells from all branches of life that removes replication errors in a strandspecific manner, such that mismatched nucleotides are preferentially removed from the newly replicated strand of DNA. Here we demonstrate a role for MMR in helping create new phenotypes in nondividing cells. We show that mispairs in yeast that escape MMR during replication can later be subject to MMR activity in a replication strand-independent manner in nondividing cells, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 28 publications
2
62
0
Order By: Relevance
“…This hypothesis is supported by two recent articles that came to a similar conclusion, though having used different approaches. In a first report (Rodriguez et al 2012), the authors used single-strand oligo-nucleotides to introduce mutations and revert a non-functional allele of the TRP5 gene in S. cerevisiae . Analysis of the recovery of Trp + revertants after transforming oligos targeting the transcribed or non-transcribed strand, in MMR-proficient or MMR-deficient strains, revealed that when mispair correction is uncoupled from DNA replication, it uses as template for repair either one of the two DNA strands, most likely due to the absence of a DNA strand discrimination signal and is therefore mutagenic.…”
Section: Mechanistic Aspects Of Mmrmentioning
confidence: 99%
“…This hypothesis is supported by two recent articles that came to a similar conclusion, though having used different approaches. In a first report (Rodriguez et al 2012), the authors used single-strand oligo-nucleotides to introduce mutations and revert a non-functional allele of the TRP5 gene in S. cerevisiae . Analysis of the recovery of Trp + revertants after transforming oligos targeting the transcribed or non-transcribed strand, in MMR-proficient or MMR-deficient strains, revealed that when mispair correction is uncoupled from DNA replication, it uses as template for repair either one of the two DNA strands, most likely due to the absence of a DNA strand discrimination signal and is therefore mutagenic.…”
Section: Mechanistic Aspects Of Mmrmentioning
confidence: 99%
“…Although a low level of MMR has been detected in nondividing cells, it lacks strand discrimination, presumably because the normal link with replication is missing (Rodriguez et al 2012). Such residual MMR, however, may provide a mechanism to introduce a potentially beneficial change into both strands of duplex DNA under stress conditions.…”
Section: Pcna Sliding Clampmentioning
confidence: 99%
“…However, biochemical experiments have also shown that MutLα can be activated on relaxed closed circular (RCC) heteroduplex DNA, which contains a small region of unpaired helix that can serve as a site for clamp loading, but in this case, endonuclease action occurs on either strand (9). This reaction provides a potential mechanism for activation of MMR on nonreplicating DNA and is of interest because recent studies indicate that undirected MMR occurring outside of replication can lead to mutation production (11,12).…”
Section: +mentioning
confidence: 99%